Differences and similarities in stand characteristics after prescribed burning and wildfire : implications for conservation of forest biodiversity - Jakob, Hannah Sophie (SLU/Dept. of Ecology, 2023)
1. Wildfires are a natural disturbance in the boreal forests of Fennoscandia and have shaped and formed forests in the past, resulting in very heterogeneous forests containing large amounts of dead and living trees in various age classes. Over the past centuries, forest management simplified forests, so that they today are much less variable than historically. Further, the economic value of timber has incentivized more effective fire suppression methods. As a result, fire events have become rare and together with the effects of industrial forestry led to a decline of forest-dwelling species. Those species depend on the heterogeneity and structures which today sparsely occur. Today, prescribed burning is seen as an effective tool to restore forests that lost their historical values. 2. In this study, I describe and compare differences and similarities between natural fires and prescribed burnings in Sweden. Further, I identify if, and which goals of prescribed burnings can be reached. For goals that are difficult or not possible to achieve with prescribed burning, I present what changes that may improve the results of prescribed burning and what possible alternative measures can be undertaken to achieve such goals. 3. Data was collected in the summer of 2022 in ten areas within the wildfire area around Kårböle, Ljusdal, in central Sweden, as well as in ten prescribed burns in Gävleborg, Västernorrland, Dalarna, and Jämtland county. 4. Wildfires and prescribed burnings generate significantly different outcomes for most variables studied. Pine mortality was 93% greater in the wildfire sites. Sites that were exposed to wildfire had up to 276% higher volumes of coarse woody debris than sites exposed to prescribed burning. Regeneration of Populus tremula, Salix caprea, Betula spp., and Pinus sylvestris was significantly higher in wildfire sites and was, depending on species, 202% to 875% greater in the latter. The proportion of fire-killed birches with fruit bodies of Daldinia loculata was more than 26 times as high ...